Obtaining Cocrystals by Reaction Crystallization Method: Pharmaceutical Applications - Isabela Fanelli Barreto Biscaia; Samantha Nascimento Gomes; Larissa Sakis Bernardi; Paulo Renato Oliveira (Pharmaceutics, 2021)
Cocrystals have gained attention in the pharmaceutical industry due to their ability to improve solubility, stability, in vitro dissolution rate, and bioavailability of poorly soluble drugs. Conceptually, cocrystals are multicomponent solids that contain two or more neutral molecules in stoichiometric amounts within the same crystal lattice. There are several techniques for obtaining cocrystals described in the literature; however, the focus of this article is the Reaction Crystallization Method (RCM). This method is based on the generation of a supersaturated solution with respect to the cocrystal, while this same solution is saturated or unsaturated with respect to the components of the cocrystal individually. The advantages of the RCM compared with other cocrystallization techniques include the ability to form cocrystals without crystallization of individual components, applicability to the development of in situ techniques for the screening of high quality cocrystals, possibility of large-scale production, and lower cost in both time and materials. An increasing number of scientific studies have demonstrated the use of RCM to synthesize cocrystals, mainly for drugs belonging to class II of the Biopharmaceutics Classification System. The promising results obtained by RCM have demonstrated the applicability of the method for obtaining pharmaceutical cocrystals that improve the biopharmaceutical characteristics of drugs.